Influence of Continuous Nursing on the Psychological State and Coping Style of Patients Undergoing Pacemaker Implantation - Xin LIU; Xu HE; Ling LI; Lili HUANG; Zhaojun LIU (Iranian Journal of Public Health, 2015)
Background: Patients undergoing pacemaker implantation often experience anxiety and fear. As such, studies have focused on the mechanisms that relieve the negative emotions caused by the intervention. Continuous nursing is a safe and effective nursing mode. In this study, continuous nursing intervention was provided for elderly patients undergo-ing pacemaker implantation and an empirical investigation was performed to determine the effects of their negative emotion and disease-coping ability.